Reversible dioxygen binding in solvent-free liquid myoglobin - Perriman, Adam W.; Brogan, Alex P.S.; Cölfen, Helmut; Tsoureas, Nikolaos; Owen, Gareth R.; Mann, Stephen (Nature Chemistry, 2010)
The ensemble of forces that stabilize protein structure and facilitate biological function are intimately linked with the ubiquitous aqueous environment of living systems. As a consequence, biomolecular activity is highly sensitive to the interplay of solventĝ€"protein interactions, and deviation from the native conditions, for example by exposure to increased thermal energy or severe dehydration, results in denaturation and subsequent loss of function. Although certain enzymes can be extracted into non-aqueous solvents without significant loss of activity, there are no known examples of solvent-less (molten) liquids of functional metalloproteins. Here we describe the synthesis and properties of room-temperature solvent-free myoglobin liquids with near-native structure and reversible dioxygen binding ability equivalent to the haem protein under physiological conditions. The realization of room-temperature solvent-free myoglobin liquids with retained function presents novel challenges to existing theories on the role of solvent molecules in structural biology, and should offer new opportunities in protein-based nanoscience and bionanotechnology. © 2010 Macmillan Publishers Limited. All rights reserved.